Analisis Data Transaksi untuk Penempatan Produk Prioritas Oli Motor Menggunakan Algoritma Apriori - Gigih Prima Subakti; Yessica Nataliani (P3M Politeknik Negeri Bengkalis, 2022)
Data mining is a process of finding essential and unique information, as well as operational business management that requires knowledge to increase the effectiveness and efficiency of the company. CV. XYZ is a bicycle and motorcycle spare parts shop located in West Java since 1999 and has had a transaction management system since 2012. However, the system is only used for recording and archiving, which should be used more optimally to improve the quality of operational management. The management of the layout of goods is not well planned by CV. XYZ, which should be able to be analyzed with existing transaction data. Therefore, this study focuses on transaction analysis to determine the layout of goods using the a priori algorithm with a minimum support of 4% and a minimum confidence of 50%. The research produces 21 association rules that can be used as a priority product placement on the CV. XYZ with a matcging percentage of 57.1% for the minimum support and confidence that has been tested.